PENGARUH BUDAYA SEKOLAH TERHADAP KUALITAS PROSES PEMBELAJARAN (PIONIR: JURNAL PENDIDIKAN, 2021)
School culture is the hallmark, character or character and image of the school. Schools as the main indicator to direct the educational output process that is oriented towards the creation of a good quality learning process, in summary this study aims to provide an overview of the climatic conditions and school culture that affect the quality of the learning process and this researcher tries to examine these conditions by conducting research using ex-post facto quantitative method with prerequisite test and ANOVA test which shows the result of the ANOVA test is 0.000. The results of this study note that the significance of 0.000> 0.05, it can be concluded that school culture has a significant effect on the quality of the learning process.